Insights Into a Hypercoagulable Case of Thyrocardiac Disease and Literature Overview - Pin-Yi Wu; Ruchika Meel (Annals of Internal Medicine: Clinical Cases)
Hyperthyroidism is associated with a hypercoagulable state and has been described previously in case studies in the context of cerebral vein thrombosis and pulmonary emboli. In this case report, we present a middle-aged man with a rare combination of rheumatic mitral valve disease and thyroid storm complicated by enormous intracardiac thrombus burden. We aim to highlight the hypercoagulable state associated with thyrocardiac disease and to alert the physician to remain vigilant for not only this clinical entity but also for multiple disease states occurring in 1 patient.